2016
DOI: 10.4236/abcr.2016.53013
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study of the Knowledge and Practice of Self-Breast Examination among Market Women at the Makola Shopping Mall, Accra, Ghana

Abstract: Background: Breast cancer is one of the most common cancers in women worldwide. With an estimated incidence of 1,676,633 with 521,817 deaths in the year 2012, the figure is expected to hit the 82.5 millionth mark by 2015. Breast cancer screening is reported to be extremely low in most low-middle income countries like Ghana. This study was to determine the knowledge and practices of self-breast examination among market women at Makola Shopping Mall in Accra, Ghana. Methods: The study was conducted at the Makola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 30 publications
4
30
1
Order By: Relevance
“…This finding is comparable to studies conducted in Nigeria, Saudi Arabia, and Ghana [ 17 19 ], where low practice has also been reported. However, our finding is in contrast with the findings from a study among Ghanaian market women where 64.0% were reported to practice BSE once a month [ 20 ]. This could be due to the fact that most market women are older and are much more aware that being postmenopausal is a risk factor for breast cancer and would want to detect the condition early.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is comparable to studies conducted in Nigeria, Saudi Arabia, and Ghana [ 17 19 ], where low practice has also been reported. However, our finding is in contrast with the findings from a study among Ghanaian market women where 64.0% were reported to practice BSE once a month [ 20 ]. This could be due to the fact that most market women are older and are much more aware that being postmenopausal is a risk factor for breast cancer and would want to detect the condition early.…”
Section: Discussioncontrasting
confidence: 99%
“…A huge number of the study participants had never performed a BSE, with majority of those who never performed being SHS students. An observation attributed to their lack of knowledge on the right procedure for the examination, a finding similar to reports from other comparable studies [ 9 , 14 , 20 22 ]. This study is limited by the fact that there was no question asking if students have received training on how to perform BSE, except for nursing students who are trained as part of their academic and professional practice.…”
Section: Discussionsupporting
confidence: 87%
“…Fewer respondents were aware that mammography is a screening modality. These findings were comparable to a study done in Ghana which found that 93% of the study participants were aware of self-breast examination as a screening modality (34). The findings are significantly higher compared to Agwu et.al, (24) who found that 38.9% of respondents were aware that self-breast examination was screening tool, 13% were aware of clinical breast examination and 13.4% were aware of mammography as a screening technique.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that having perceived susceptibility to breast disease increased the likelihood of practice of BSE. The most common barrier to practice of BSE reported by many of the studies in this review was lack of knowledge of BSE technique 1626293234. Efforts must be put in place to overcome this barrier through intensive health education programs, preferably involving the media.…”
Section: Discussionmentioning
confidence: 99%